Significance of teaching of microcomputer technology through practical robotic ground vehicle application - Md Fahmi, Abd Samad; Zainal, Zairulazha; Jamaluddin, Hishamuddin (Springer Nature, 2025)
Teaching the technology behind microcomputers to beginner students can be challenging due to the fundamental knowledge they need to grasp. Students must understand what happens in the “brain” of microcomputers to comprehend the complexities of the technology. This paper outlines a pragmatic approach that includes a practical implementation of problem-solving techniques for a microcomputer course, focusing on a robotic ground locomotive vehicle as the application. This involved assembling and seamlessly integrating mechanical, electrical, and microcontroller elements, using two software programs: Flowcode and Proteus. Evaluation of the implementation’s efficacy includes quantitative and qualitative measures. Results were evaluated based on achievements throughout the course, and students’ feedback was gathered through a questionnaire at the end of the course. Various aspects were assessed through the questionnaire, including the effect of the practice on students’ understanding, the alignment with the curriculum, and how the practice boosted students’ interest in the field. The analysis showed that the approach had a very positive impact on students, with an average score of 4.16 for application relevance and 4.29 for overall student involvement, based on a Likert scale ranging from 1 (strongly disagree) to 5 (strongly agree). Most students recommended continuing the exercise, with the most common rating being 5 (strongly agree). The findings underscore the value of hands-on, application-oriented pedagogies in facilitating effective learning experiences within microcomputer education.